Work and the disability transition in 20th century America - Wilson, Sven; Burton, Joseph; Howell, Benjamin (National Bureau of Economic Research, 2005)
"Using data from Union Army pensioners and from the National Health Interview Surveys, we estimate that work-disability among white males aged 45-64 was 3.5 times as high in the late 19th century than at the end of the 20th century, including a decline and flattening of the age-profile since 1970. We present a descriptive model of disability that can account for a) the secular decline in prevalence; b) changes in slope of the age-profile; and c) periods of increasing prevalence. The high level and relatively flat slope of the historical disability age-profile is consistent with the early onset of chronic conditions and with high mortality associated with a subset of those conditions. We show that many common conditions in the 19th century have been either eliminated, delayed to later ages, or rendered less disabling by treatment innovations and the transformation of the workplace. These improvements have swamped the effect of declining mortality, which put upward pressure on disability prevalence. Given the low rate of mortality prior to age 65, technological changes will likely induce further reductions in work-disability, though recent increases in the prevalence of asthma and obesity may eventually work against this trend"--National Bureau of Economic Research web site.
Keywords: Geschichte; Wirtschaft; People with disabilities -- United States -- Economic conditions; People with disabilities -- United States -- History; USA